2018
DOI: 10.1097/aln.0000000000002196
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-phosphate Receptor 2 Signaling Promotes Caspase-11–dependent Macrophage Pyroptosis and Worsens Escherichia coli Sepsis Outcome

Abstract: What We Already Know about This Topic What This Article Tells Us That Is New Background Pyroptosis, a type of proinflammatory programmed cell death, drives cytokine storm. Caspase-11–dependent macrophage pyroptosis contributes to mortality during sepsis. Sphingosine-1-phosphate receptor 2 (S1PR2) signaling can amplify interleukin-1β secretion in endotoxin-induced inflammation. Here, we hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…It is demonstrated that RAPA can reduce the pyroptosis in various cell models [ 18 20 ] and inhibition of pyroptosis prolong the survival of a sepsis animal model [ 4 , 9 11 ]. In the present study, we found that RAPA inhibited pyroptosis and reduced the septic response in both LPS-induced HUVECs and PMA+LPS-activated human THP-1 cell models of sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is demonstrated that RAPA can reduce the pyroptosis in various cell models [ 18 20 ] and inhibition of pyroptosis prolong the survival of a sepsis animal model [ 4 , 9 11 ]. In the present study, we found that RAPA inhibited pyroptosis and reduced the septic response in both LPS-induced HUVECs and PMA+LPS-activated human THP-1 cell models of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that pyroptosis is the trigger of the cytokine storm seen at the beginning of sepsis [4,8]. In addition, knockout of the gene encoding the pyroptotic protein Gasdermin D (GSDMD) and overexpression of autophagyrelated proteins can effectively inhibit pyroptosis and prolong the survival of a sepsis animal model [4,[9][10][11]. Kim et al found that microglial cells infected with Streptococcus pneumoniae overexpressed the autophagy-related proteins and exhibited low levels of pyroptosis, while inhibition of autophagy in the infected cells upregulated caspase-1 and increased IL-18 release [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify AM pyroptosis, gating was based on F4/80-positive cells, allowing analysis of fluorescently labeled active caspase-1 (FLICA) and propidium iodide. In this approach, F4/80 + FLICA + PI + cells appeared in the upper right quadrant of the FLICA-PI plot and were considered to be pyroptotic AMs [ 29 ]. Flow cytometry was conducted using an LSR2 flow cytometer (BD Biosciences), and raw data were analyzed using FlowJo software (TreeStar Corporation, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Isotype control antibody (Immuno Chemistry Technology, USA) was used as negative control. FACS gating strategy for indicating macrophage pyroptosis was that F4/80 positive cells were gated to analyze uorescently labeled active caspase-1 (FLICA) and propidium iodide then F4/80+FLICA+PI+ cells were presented in the up-right region of FLICA-PI plot and indicated as AMs pyroptosis [29]. Flow cytometry analysis was conducted with a BD LSR2 ow cytometer (BD Biosciences).…”
Section: Flow Cytometrymentioning
confidence: 99%